Co-Lateral Effect of Octenidine, Chlorhexidine and Colistin Selective Pressures on Four Enterobacterial Species: A Comparative Genomic Analysis - Mathilde Lescat; Mélanie Magnan; Sonia Kenmoe; Patrice Nordmann; Laurent Poirel (MDPI AG, 2021)
Bacterial adaptation to antiseptic selective pressure might be associated with decreased susceptibility to antibiotics. In Gram-negative bacteria, some correlations between reduced susceptibility to chlorhexidine (CHX) and polymyxins have been recently evidenced in Klebsiella pneumoniae. In the present study, four isolates belonging to distinct enterobacterial species, namely K. pneumoniae, Escherichia coli, Klebsiella oxytoca and Enterobacter cloacae, were submitted to in-vitro selective adaptation to two antiseptics, namely CHX and octenidine (OCT), and to the antibiotic colistin (COL). Using COL as selective agent, mutants showing high MICs for that molecule were recovered for E. cloacae, K. pneumoniae and K. oxytoca, exhibiting a moderate decreased susceptibility to CHX, whereas OCT susceptibility remained unchanged. Using CHX as selective agent, mutants with high MICs for that molecule were recovered for all four species, with a cross-resistance observed for COL, while OCT susceptibility remained unaffected. Finally, selection of mutants using OCT as selective molecule allowed recovery of K. pneumoniae, K. oxytoca and E. cloacae strains showing only slightly increased MICs for that molecule, without any cross-elevated MICs for the two other molecules tested. No E. coli mutant with reduced susceptibility to OCT could be obtained. It was therefore demonstrated that in-vitro mutants with decreased susceptibility to CHX and COL may be selected in E. coli, K. pneumoniae, K. oxytoca and E. cloacae, showing cross-decreased susceptibility to COL and CHX, but no significant impact on OCT efficacy. On the other hand, mutants were difficult to obtain with OCT, being obtained for K. pneumoniae and E. cloacae only, showing only very limited decreased susceptibility in those cases, and with no cross effect on other molecules. Whole genome sequencing enabled deciphering of the molecular basis of adaptation of these isolates under the respective selective pressures, with efflux pumps or lipopolysaccharide biosynthesis being the main mechanisms of adaptation.